TINGKAT PARTISIPASI SISWA DALAM PEMBELAJARAN FISIKA SECARA DARING PADA MASA PANDEMI COVID-19 KELAS XI SMAN 1 SABAK AUH - Novi Karollina; Zulirfan Zulirfan; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Student's participation in the online physics learning is not known with certainty. Therefore, a research was carried out to determine student’s participation in online physics learning on dynamic fluid material of class XI SMAN 1 Sabak Auh. The location in research at SMAN 1 Sabak Auh, Kecamatan Sabak Auh, Kabupaten Siak. The participant in research were 40 students of class XI IPA SMAN 1 Sabak Auh. The research was conducted from November 2020 to March 2021. The data collection technique in research was through documentation study. The research data was the results of analysis student activity checklist in the process of implementing and evaluating online physics learning on dynamic fluid material. The results obtained from this study indicate that the level of student participation in the implementation process and online learning through Google Classroom is in the sufficient category. The average score of the students in the learning implementation process was 1.65 and the standard deviation was 0.60. Meanwhile, the average score of the students in the learning evaluation was 1.63 and the standard deviation was 0.65.Keywords: Online Learning, Student’s Participation